PENGELOLAAN WAKAF TUNAI - Muhyar Fanani (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
Basic issue on waqaf is the management, especially on the management of cash money. The institutions having in charge for managing the waqaf of cash money, have some management specific characteristics and patterns. This study focused on the management of waqaf on cash money in three institution, TWI, PKPU, and BMM. Applying qualitative method, it is found that waqaf of cash money still has some problems to solve: the lack of dissemination about waqaf of cash money among society members, the lack of professional nāẓir, no effective fundraising system, the weak managerial system, the low commitment on risk management, the unprotected purchasing power of money, and the variability on the distribution priority.